Attention to Diversity from an Interdisciplinary Perspective: Results from the Final Graduation Project from a Group of Students Majoring in Preschool Education and Special Education - Paola Delgado-Obregón; Grettel Hernández-Barboza; Heidy León-Arce; Laura Morera-Calvo; Silvia Elena Morera-Villarebia; Roxana Obregón-Vargas (Revista Electrónica Educare)
Nowadays, the topic of diversity is being studied, particularly in the field of the formation of future educators, where it is clearly evident in each one of the students. In order to understand this concept and meet the challenges it demands, this investigation, through the experience of action research, looks for a real picture of how this diversity is served in Guanacaste’s rural contexts. This is accomplished by identifying those ways to guide a better teachers’ work, and by taking into account the educational planning and the participation of the different sectors involved in the process of teaching and learning.